1992
DOI: 10.1073/pnas.89.1.378
|View full text |Cite
|
Sign up to set email alerts
|

Viral proteins associated with the Epstein-Barr virus transactivator, ZEBRA.

Abstract: The BamHI Z Epstein-Barr replication activator (ZEBRA) mediates disruption of latency and induction of Epstein-Barr virus (EBV) early gene expression in latently infected lymphocytes. Polyclonal rabbit sera raised against ZEBRA were used to immunoprecipitate ZEBRA-associated proteins (ZAPs). ZAPs of 19, 21, 23, and 42 kDa were coimmunoprecipitated with ZEBRA from extracts of EBVproducing lymphoid cell lines. ZAPs were not recognized directly by the rabbit sera, but they were antigenic for EBV+ human sera. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…2A). After autoradiography of 35 S-labeled immunoprecipitates it was found that ZEBRA mutants that carried an alanine substitution at S186 were expressed to higher levels than wild-type ZEBRA (compare lanes 7 and 8 with lane 6). However, 32 P labeling indicated that mutations of S167 and S173 to alanine reduced but did not abolish the overall level of phosphorylation (compare lane 4 with lane 3).…”
Section: Ck2mentioning
confidence: 99%
See 3 more Smart Citations
“…2A). After autoradiography of 35 S-labeled immunoprecipitates it was found that ZEBRA mutants that carried an alanine substitution at S186 were expressed to higher levels than wild-type ZEBRA (compare lanes 7 and 8 with lane 6). However, 32 P labeling indicated that mutations of S167 and S173 to alanine reduced but did not abolish the overall level of phosphorylation (compare lane 4 with lane 3).…”
Section: Ck2mentioning
confidence: 99%
“…As no lysine or arginine residues are present between S167 and S173, the two residues are located on the same tryptic peptide. This tryptic peptide can be detected in a peptide map of 35 Slabeled ZEBRA due to the presence of a cysteine residue at position 171. We compared the migration of 35 S-labeled tryptic peptides of Z(S186A) and Z(C171A/S186A) with phosphopeptides A and D, the phosphopeptides that disappeared when S167 and S173 were mutated to alanine (Fig.…”
Section: Ck2mentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptional activation of recombinant ori Lyt was utilized to drive a reporter construct in Raji cells underlying inducing culture conditions. BZLF 1 plays the key role in the transmission of inducing signals from the host cell towards the replicative activation of the viral genome [15,17,26]. Besides up-regulation of viral regulatory genes in a cascade-like manner, direct trans-activation of oriLyt by the BZLF 1 product was reported [7,13].…”
Section: Introductionmentioning
confidence: 99%